Assessment of Quality of Life in Coronary Artery Disease Patients Using who QOL Bref - Adeel Ahmed, Muhammad Muneeb, Attaullah Khan Niazi, Kanza Sana Umer, Zanib Javed Chatha, Sana Rasheed, (Pakistan Journal of Medical & Health Sciences, 2022)
Study Objective: The objective of my study is assess the quality of life in coronary artery disease patients using WHO QoL BREF and to identify the different variables and factors which are affecting the quality of life in CAD patients in our population in general and the economic progress of the country in particular. Material & Methods: The study design will be cross-sectional and purposive sampling technique will be used. The study population will be the patients presenting in cardiology OPD of Shalamar hospital & Punjab Institute of Cardiology Lahore. Inclusion criteria will be the patients of both sexes above 30 years and exclusion criteria will be the patients with ailments other than coronary artery diseases. Results: A total of 611 CAD patients includes in for the research. 305 from Public & 306 from private hospital. Mean age was 56 years out of which 377 (61.7%) were male patients and 234 (38.3%) were females. Out of 611 patients that were included in the study 19 (3.1%) rated their quality of life very poor; 265 (43.4%) poor; 200 (32.7%) neither poor nor good & 127 (20.8%) good. Conclusion: The study showed life’s quality and general wellbeing, with the majority of patients having a "poor" life’s quality . The relationship among quality of life and patients' perceptions of health and age was statistically significant.